Responsive Microgels through RAFT-HDA Dynamic Covalent Bonding Chemistry - Jingkai Nie; Hang Yin; Ruyue Cao; Changyuan Huang; Xiang Luo; Jun Ji (Molecules, 2024)
This paper developed a method for preparing ultrasound-responsive microgels based on reversible addition fragmentation chain transfer-hetero Diels–Alder (RAFT-HAD) dynamic covalent bonding. First, a styrene cross-linked network was successfully prepared by a Diels–Alder (DA) reaction between phosphoryl dithioester and furan using double-ended diethoxyphosphoryl dithiocarbonate (BDEPDF) for RAFT reagent-mediated styrene (St) polymerization, with a double-ended dienophile linker and copolymer of furfuryl methacrylate (FMA) and St as the dienophile. Subsequently, the microgel system was constructed by the HDA reaction between phosphoryl disulfide and furan groups using the copolymer of polyethylene glycol monomethyl ether acrylate (OEGMA) and FMA as the dienophore building block and hydrophilic segment and the polystyrene pro-dienophile linker as the cross-linker and hydrophobic segment. The number of furans in the dienophile chain and the length of the dienophile linker were regulated by RAFT polymerization to investigate the effects of the single-molecule chain functional group degree, furan/dithioester ratio, and hydrophobic cross-linker length on the microgel system. The prepared microgels can achieve the reversible transformation of materials under force responsiveness, and their preparation steps are simple and adaptive to various potential applications in biomedical materials and adaptive electrical materials.